Mentalizing impairment as a mediator between reported childhood abuse and outcome in nonaffective psychotic disorder. (January 2018) - Weijers, J.; Fonagy, P.; Eurelings-Bontekoe, E.; Termorshuizen, F.; Viechtbauer, W.; Selten, J.P.
Abstract: Reported childhood abuse has been linked to the severity of clinical symptoms and social dysfunction in non-affective psychotic disorder. Impaired mentalizing ability may be one of the mechanisms accounting for this effect. This study examined whether impaired mentalizing mediates the effect of reported childhood abuse on positive symptoms, negative symptoms, and social dysfunction. Eighty-seven patients with non-affective psychotic disorder were examined. Reported childhood abuse was measured using the Childhood Experience of Care and Abuse interview. Additionally, the Social Functioning Scale and the Positive and Negative Syndrome Scale were used. The Hinting Task was used to measure mentalizing impairment. Reported childhood abuse was significantly related to the severity of positive and negative symptoms, not to social dysfunction. Reported childhood abuse was also related to mentalizing impairment. Mentalizing impairment was related to negative symptoms, but not to positive symptoms or social dysfunction. Mentalizing impairment accounted for 40% of the association between reported childhood abuse and negative symptoms, indicating partial mediation. A sensitivity analysis revealed that the mediating effect was only observed in those who reported fairly severe childhood abuse. Highlights: Childhood abuse was observed to be related to positive as well as negative symptom severity. Mentalizing impairment was a partial mediator between childhood abuse and negative symptoms. No such mediation effect was found regarding positive symptom severity and social dysfunction.